ПРОБЛЕМНІ ПИТАННЯ ЛІЦЕНЗУВАННЯ СТРАХОВОЇ ДІЯЛЬНОСТІ В УКРАЇНІ - Dergunov, D.S. (V. Mamutov Institute of Economic and Legal Research of the National Academy of Sciences of Ukraine, 2009)
The article considers the problems concerning nonconformity of a by-law to general and special laws which regulate insurance activity in Ukraine. The author offers to introduce amendments to the current legislation on licensing insurance activity in Ukraine.